Penerapan Three Sided Side Match Method Untuk Penyisipan Pesan Pada Audio - Dony Dharmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The wider the use of the internet network, the more vulnerable a sender of information is to wiretapping that can change the authentication and integrity of the data. Often someone who wants to send a message to someone else, does not want the message to be known by others. Usually the contents of the message are very confidential, which can only be known between the sender and the recipient of the message or a limited circle. To solve the problems described above, an application will be built to insert messages into audio using the Microsoft Visual Studio 2010 programming language that is able to insert messages into audio by implementing the Three Sided Side Match Method. This research is also expected to be able to maintain the confidentiality of messages inserted into an audio file so that there is no data leakage to unwanted parties because it is confidential and avoids wiretapping of information contained in the audio when exchanging information online.